Hydrogen production from aluminum-water reactions at low Temperatures: based on an in-situ two powders of different particle sizes - Zhang, Xiaoliang; Wang, Li; Tao, Guangyuan; Guo, Ronghan; Fang, Jiawei; Zhang, Jun; Mao, Haifang (Frontiers in Energy Research, 2024)
Abstract：To investigate the granule reaction of two-micron aluminum powders with water at low temperatures, differential scanning calorimetry (DSC) was used to analyze the initial exothermic temperature. Additionally, adiabatic accelerated calorimetry (ARC) was employed to study the exothermic reaction under adiabatic conditions. The hydrogen production and particle size variation were investigated in order to gain insights into the Al-water reaction in a reactor with no induction time. Through focused beam reflectance measurement (FBRM) analysis, it was observed that during the reaction process of Al-water, particle sizes initially increased and then decreased. Specifically, the particle size of 3µm aluminum powder experienced a 189% increase after the reaction while 25µm aluminum powder decreased by 29%. Ultimately, both types of particles reached similar final sizes around 13.89µm. The process of Al-water reaction was explained and hydrogen production was analyzed, and the kinetic model was obtained.